THE PREVENTIVE EFFECT AND ENHANCE IMMUNITY FUNCTION OF BU-ZHONG-YI-QIWAN ON S180 TUMOR MICE. - Hu, Fang; Liu, Xiaoya; Chen, Xinyue; Li, Can; Zhu, Ruijuan; Han, Huan; LI, Yingdong; Feng, Shilan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: To evaluate the preventive effect and enhance immunity functions of Bu-zhong-yi-qi wan in vivo.Materials and Methods: S180 tumor mice model was established by subcutaneous injection a dose of 0.2 ml (1×107/ml) at the rightoxter. The inhibitory rates, spleen indexes and thymus indexes were calculated. Splenic lymphocyte proliferative activity assay andphagocytosis activity of peritoneal macrophages were done. Interferon (IFN-γ), interleukin (IL-2) and tumor necrotic factor (TNF-α) inserum were detected.Results: In the S180 tumor-bearing mice, Bu-zhong-yi-qi wan with medium-dose (975 mg/kg, 100 mg/l) had potent preventive effect andanti-tumor effect, macrophage phagocytosis and Con A-stimulated splenocyte proliferation were increased as compared with modelcontrol treatment. Bu-zhong-yi-qi wan could take part in the immune response by promoting the proliferation and differentiation of Tcells,increasing the activity of the macrophages, inducing the generation of cell factor IL-2, TNF-α, IFN-γ.Conclusion: It proved that Bu-zhong-yi-qi wan of medium-dose had great preventive effect and could enhance immunity function.